Strain-induced enhancement of carrier mobility and optoelectronic properties in antimonene/germanane vdW heterostructure - Yan, Jie; Cao, Dan; Yang, Xue; Wang, Jianfeng; Jiang, Zhouting; Jiao, Zhiwei; Shu, Haibo (Applied physics. A, Materials science & processing, 2022)
By means of first-principles calculations, we report the in-plane strain effect on the structural stability, electronic structures, and optical properties of antimonene/germanane van der Waals heterostructure achieved by vertically stacking antimonene and germanene monolayers. The antimonene/germanane heterostructure with type-II band alignment has an indirect band gap of 1.38 eV. The band gap, band alignment, carrier mobility, and optical absorption coefficient of the heterostructure can be tuned by loading in-plane strain. In particular, the in-plane strain can drive multiple indirect–direct–indirect band gap transitions and the band-edge alignment from type-I to type-II. Moreover, the heterostructure exhibits increased hole mobility and ultra-high electron mobility up to 3 × 10 4 cm 2 V −1 s −1 under the tensile strain of 4%. These findings suggest large potential of antimonene/germanane heterostructure for electronic and optoelectronic applications.